Einstein-Hetze (1920)
An article clipping from the Frankfurter Zeitung regarding the controvery surrounding Albert Einstein's Theory of Relativity. The Frankfurter Zeitung was a German-language newspaper published from 1856 to 1943.
Keywords: Einstein, Albert, 1879-1955; Clippings (Books, newspapers, etc.); Hesse, Hermann, 1877-1962; Frankfurter Zeitung und Handelsblatt (Frankfurt am Main, Germany : Daily)